Quality of Genipa Spruceana steyerm seedlings submitted to fertigation - Souza, Luciano Maria de [UNESP]; Rossi, Fernando Saragosa [UNESP]; Caione, Gustavo; Oliveira, Pedro Paulo Gomes de; Bertolino, Nayara (Revista de Agricultura Neotropical, 2022)
Jenipapo (Genipa spruceana) is a native species of the Amazon that has great potential in producing seedlings for reforestation. This study aimed to evaluate the effect of nutrient doses applied through fertigation on the quality of Genipa spruceana. The experimental design was completely randomized with five replications, totaling seven treatments. The treatments were: control (without fertilization); 900 mg N L-1 and 750 mg K L-1 with and without micronutrients; 1800 mg N L-1 and 1500 mg K L-1 with and without micronutrients, 3600 mg N L-1 and 3000 mg K L-1 with and without micronutrients. The experiment was conducted in a greenhouse for 35 days. Then, the following variables were evaluated: stem diameter, height, root and shoot dry matter, and total dry matter. From these measurements, the following ratios were calculated: height/stem diameter, height/shoot dry matter, shoot dry matter/root dry matter, and Dickson quality index. Weekly fertigation applying 1800 mg N -1 and 1500 mg K L-1 provided the best Dickson Quality Index of Genipa spruceana seedlings. The hypothesis of the present study was confirmed, and the Genipa spruceana did not have a tolerance to high N e K fertilization.
Keywords: Amazon; Dickson Quality Index; Forest essences